The codrug approach for facilitating drug delivery and bioactivity. (1st September 2016) - Aljuffali, Ibrahim A.; Lin, Chwan-Fwu; Chen, Chun-Han; Fang, Jia-You
ABSTRACT: Introduction : Codrug or mutual prodrug is a drug design approach to chemically bind two or more drugs to improve therapeutic efficiency or decrease adverse effects. The codrug can be cleaved in the body to generate parent actives. The codrug itself can be inactive, less active, or more active than the parent agents. It has been demonstrated that codrugs possess some benefits over conventional drugs, including enhanced solubility, increased permeation for passing across biomembranes, prolonged half-life for extending the therapeutic period, and reduced toxicity. Areas covered : This review article describes the history, design strategy, and potential applications of codrugs. Codrugs are predominantly used to treat some conditions such as neurodegenerative, cardiovascular, cancerous, infectious, and inflammatory disorders. Many codrugs are developed to increase lipophilicity for better transport into/across biomembranes, especially the skin and cornea. A targeted delivery of codrugs to specific tissues or organs thus can be achieved to promote bioavailability. The chemical and enzymatic hydrolysis, bioactivity, and pharmacokinetics of codrugs are systematically introduced in this review. Expert opinion : Additional profiles pertaining to clinical trials will support further applicability of codrug therapy. Caution should be used in optimizing the benefits of codrugs to ensure a balance between damage or toxicity and the effectiveness of delivery enhancement.